PERSPEKTIF PEMASARAN: STRATEGI GLOBAL ATAU REGIONAL? - Werner Ria Murhadi (Journal of Management and Business, 2003)
Although in both economic literatures and practices the most frequently used catchword is "globalization ", the current company environment in reality is not characterized by such worldwide multilaterally or an increasing degree of homogeneity in customer tastes. Recent research suggests that globalisasi is a myth. Far from taking place in a single global market, most business activities by large firms take place in regional blocks especially in AFT A, NAFTA, and European Union. Nevertheless, some indications point to a transition from regionalization to globalisasi in the long run.